MILITARY-POLITICAL ACTIVITY IN THE CASPIAN IN THE POST-SOVIET PERIOD (Legal Aspects) - MAMEDOV, Rustam (CENTRAL ASIA AND THE CAUCASUS, 2007)
Military presence at seas and lakes is one of the most acute and complicated problems of international relations and international law. In the past few years, this problem has acquired particular relevance in the Caspian basin where an arms race is escalating, new military bases are being created, and where not only Caspian but also third countries are looking to deploy their armed forces.1 Military presence in the Caspian has become desirable for many states. Naval presence is one of the forms in which countries use their naval forces beyond their state borders, in the territorial waters of other states. Both from a legal and technical perspective, naval presence is an extremely complex and dynamic system of interstate relations and military ties.2 According to G.S. Gorshkov and G.M. Melkov, naval presence, in a particular part of the World Ocean, can be either constant or occasional, accompanied by actions (operations) by a country (a group of countries), designed to accomplish certain foreign policy goals. The content of these goals is predetermined by the foreign policy and military strategy of states under whose flag naval forces are operating. Naval presence, they continue, “is an element of military presence—i.e., the presence of military contingents of foreign countries (ground, air and naval forces) on the territory of other states and in various parts of the World Ocean.”3 Naval presence is not so much a military as political and legal problem, which is of interest to all competing countries. It is connected—more than any other form of state activity at seas and lakes— with their political, economic, and military-strategic interests in the World Ocean. Naval presence fully reveals the character, foreign policy goals, and military objectives of countries that use their navies in particular parts of the world